Resposta do transporte mucociliar, função autonômica e força muscular de pacientes com doença pulmonar obstrutiva crônica submetidos a um treinamento resistido - Nicolino, Juliana [UNESP] (2014)
Studies have described the behavior of HRV after aerobic exercise, but there are few studies that show the response of the autonomic function after resistance exercise in COPD patients. In addition there is no information concerning the behavior of the mucociliary transport after resistance training in these patients. Aim: To evaluate the cardiac autonomic modulation via HRV after an acute session of resistance exercise applied at different intensities in COPD, and to evaluate and evaluate and compare the effects of resistance training on mucociliary clearance, autonomic modulation and muscle strength in COPD patients and healthy subjects. Methods: COPD patients underwent an acute session of resistance exercise with a intensity to 60% and another with 90% of 1RM and then evaluated regarding the autonomic modulation via HRV. In addition, they were evaluated via the mucociliary clearance of saccharin transit time test (STT), the autonomic nervous system activity via HRV and peripheral muscle strength via one repetition maximum test (1RM) before and after four, eight and 12 weeks of a resistance training Results: Regardless of exercise intensity, resistance exercise acute sessions influenced the autonomic modulation when the recovery period was compared with the baseline. An increase in SDNN index was observed throughout recovery time after the RE, as compared to baseline in both protocols: 60% and 90% 1RM. The same happened with LF and HF indices. In addition, the values of TTS in COPD patients and healthy subjects didn´t change after 12 weeks of resistance training...